2010
DOI: 10.1124/jpet.110.167908
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin Antagonizes Ethanol Inhibition in Purinergic P2X4 Receptors

Abstract: ATP-gated purinergic P2X4 receptors (P2X4Rs) are expressed in the central nervous system and are sensitive to ethanol at intoxicating concentrations. P2XRs are trimeric; each subunit consists of two transmembrane (TM) ␣-helical segments, a large extracellular domain, and intracellular amino and carboxyl terminals. Recent work indicates that position 336 (Met336) in the TM2 segment is critical for ethanol modulation of P2X4Rs. The anthelmintic medication ivermectin (IVM) positively modulates P2X4Rs and is belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 51 publications
(105 citation statements)
references
References 35 publications
12
93
0
Order By: Relevance
“…We have shown that IVM antagonizes ethanolmediated inhibition of P2X4Rs in vitro [12]. Moreover, IVM significantly reduced ethanol intake and preference in mouse models of ethanol self-administration [22].…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…We have shown that IVM antagonizes ethanolmediated inhibition of P2X4Rs in vitro [12]. Moreover, IVM significantly reduced ethanol intake and preference in mouse models of ethanol self-administration [22].…”
Section: Introductionmentioning
confidence: 81%
“…We have identified residues Asp331 and Met336 in the ectodomain-TM2 segment interface to be important for ethanol modulation, whereas residues Asn338, Ser341, Gly342, Leu346, Gly347, Ala349, and Ile356 in the TM2 segment were found to play a role in IVM modulation of the receptor [25,26]. Furthermore, we found that Met336 at the ectodomain-TM2 interface is a common site of action for both ethanol and IVM [12]. Interestingly, these sites are closely located to lateral fenestrations found in P2X4Rs that were shown to be sites for allosteric modulation of the receptor [27], including by IVM [28].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations